Symposium policy note 2: Digitalization of agricultural services and policy analysis in Egypt - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This policy note is one in a series of four notes that summarize key findings and recommendations from 32 seminars organized by IFPRI between 2016 and 2020 under the Evaluating Impact and Building Capacity Project funded by the United States Agency for International Development (USAID) and from related research done in collaboration with national and international partners in Egypt. The briefs have been prepared on the basis of a joint symposium and are intended to give policymakers and program designers in the areas of social protection, nutrition, agricultural policy, and the digitalization of agriculture a quick overview of research-based recommendations on key policy issues that will better enable Egypt to achieve several of the goals outlined in the Sustainable Development Strategy 2030. This policy note highlights how digital tools can help improve monitoring, evaluation, and extension services in Egypt’s agriculture sector and how policy analysis can be institutionalized to guide transformation of the food system and rural economies. Four recommendations are discussed: Building on ongoing efforts, continue to digitize agricultural information systems, build and link agricultural databases, and exploit new sources of data. Build on ongoing projects that develop mobile telephone applications for farmers and learn from international experiences to revitalize and digitalize agricultural extension in Egypt. Build the capacity of agricultural policy analysts within the Ministry of Agriculture and Land Reclamation and universities, using both conventional and new digital tools to provide high-quality, research-based policy advice. Promote further digitalization to improve the resilience of food systems in view of shocks, such as the COVID-19 pandemic.